A dynamic programming approach for computing similarity of the protein sequences based on continuous functions comparison - Robert K. Gevorgyan (Изд-во НАН РА)
This paper introduces a dynamic programming approach for computing "continuous" similarity of the two protein sequences. The discrete dynamic programming method considers items of each comparable sequence independently; meantime there is a strong interrelation between them. To overcome this disadvantage a "continuous" sequence comparison method is developed. Particularly, a certain continuous function is correlated to each comparable protein sequence, and then the comparison is made between those functions. Through compressions and expansions the comparable functions are brought to the most similar representation in the meaning of a certain similarity function. By this approach the sequence comparison problem is reduced to a functional maximization problem, which is numerically solved using dynamic programming method. Finally some practical results are presented with the application of described method.
Keywords: Mathematics; Computer software